2022
DOI: 10.1108/er-02-2022-0101
|View full text |Cite
|
Sign up to set email alerts
|

Union influence on change-oriented organizational citizenship behavior: evidence from China

Abstract: PurposeDespite the considerable research into China's industrial relation system, little attention has been focused on what do Chinese unions at the enterprise level do and how their daily work influences employees' work-related outcomes. Drawing on the theory of planned behavior, this paper aims to examine the impact of Chinese enterprise union practices on employees' change-oriented organizational citizenship behavior through the mediating roles of psychological safety, perceived insider status, and role bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 49 publications
(128 reference statements)
0
12
0
Order By: Relevance
“…Researchers investigating the relationship between narcissism and leadership behavior have found that narcissists-compared to non-narcissists-are more likely to self-promote and selfnominate (Hogan et al 1990) and are more likely to be leaders in general but less likely to communicate effectively with subordinates (de Vries and Miller 1985;Rosenthal and Pittinsky 2006). de Vries and Miller (1985) highlighted narcissistic leadership's duality, noting that some leaders evoke perceptions of strength, authority, and concern, whereas others evoke memories of intimidation, malevolence, and harm.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers investigating the relationship between narcissism and leadership behavior have found that narcissists-compared to non-narcissists-are more likely to self-promote and selfnominate (Hogan et al 1990) and are more likely to be leaders in general but less likely to communicate effectively with subordinates (de Vries and Miller 1985;Rosenthal and Pittinsky 2006). de Vries and Miller (1985) highlighted narcissistic leadership's duality, noting that some leaders evoke perceptions of strength, authority, and concern, whereas others evoke memories of intimidation, malevolence, and harm.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Generally, they cannot build long-term, deep relationships with others owing to their arrogance (Paulhus 1998;Rosenthal and Pittinsky 2006). They frequently disregard others' advice, take credit for their successes, blame others for their failures (Hogan et al 1990), and constantly seek validation and superiority Rhodewalt 2001a, 2001b;Rosenthal and Pittinsky 2006). However, narcissistic leaders also have a charming side as they can enhance shortterm staff motivation by exuding confidence and presenting a grand vision (Ouimet 2010).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…They often seek to establish a cooperative rapport with management to advance the Party state's objective of fostering a harmonious society [27]. According to Hu et al [28], Chinese trade unions engage with management on a frequent and routine basis as an integral facet of their daily operations. These interactions primarily aim to bolster employee resources and motivation, ultimately enhancing the bond between employees and organizations and elevating perceptions of employment quality.…”
Section: Pcb Labor Relations Climate Perception and Employee Outcomesmentioning
confidence: 99%